Sipariş üzerine çalışan orta ölçekli matbaalarda üretim planlama esaslarının belirlenmesi - Beyaztaş, Özlem (My University, 1999)
Teknoloji ile birlikte artan talepleri karşılamakta diğer sektörler gibi matbaa sektörüde değişik yöntemler denemektedir. Bu hızlı gelişimden payını alan sektörün en zor bölümünü değişik iş siparişleri alan orta ve büyük ölçekli matbaalar yükleniyor. Karmaşık yapının zorluğunu, birimlerin fazlalığını ve iş yoğunluğunu göz önüne alırsak bu tip işletmelerde en önemli birimin üretim planlama birimi olduğunu fark ediyoruz. Kimi firmalarda trafiker adıyla eleman alındığı ve bunlara ait üretim planlama formlarının bulunduğunu da söylersek üretim planlamanın ne kadar ciddi bir birim olduğu ortaya çıkmaktadır. Bu tezde genel anlamda kalite faktörünü tanımlayarak konuya giriş yapıldı. Sipariş üzerine çalışan bir matbaada iş akış diyagramı oluşturularak işlerin birimlerdeki kalış süreleri ve işlem aralıkları tespit edildi. Kolay anlaşılabilir ve uygulanabilir özelliğinin olması için gerçek bir işle açıklandı. Kullanılan formlar bu işe ait bilgilerle dolduruldu.

To remedy the requests which increase together with the technology, the sector of the printing office tries different methods like the other sectors. The sector who gets the share of this fast developing, are the middle and big creterioned printing offices who reccives different orders of work, assume responsibility the most different parts. If we take in mind, the difficulty of the complicated construction, the too many tenses and the intensity of the work we realize, that in these type of administratings the most important tens is the tens of the production planning. If we say that some firms are taken personals who are called system organiser and the production planning forms are concerning to these, it come on the scene how serious tens the production planning is. In this thesis the factor of the quality has been defined and so attemped in this subject. A printing office, which works for ordering, the statement of the period in the tenses of the works and the spaces of the procedure have been fixed after the forming of the work flow diagram. It has been explained with a real work, to have the special feature of a casy understanding and application. The used forms are filled with the information as relating to this work. The most important fixing in the end of the thesis, is to reduce the fault of the ratio to a minimum by forming the tens of the production planning.
Keywords: MATBAACILIK; ÜRETİM PLANLAMASI